Integrated laser based pre‐tempering at laser welding of AISI 1045 steel by using 3D‐scanner optics. Issue 11 (12th November 2021) - Steidle, F.; Hofele, M.; Ketzer‐Raichle, G.; Gooßen, M.; Riegel, H.
Abstract: Laser‐based pre‐heating of laser beam welding with a 3D scanning optics, applied to AISI 1045 steel, is studied. Laser beam welding of heat‐treatable steel is challenging due to martensitic hardening in combination with defects. Pre‐tempering aims the reduction of the cooling rates and martensitic microstructure within the weld seam. An oscillating defocused laser beam was guided over the surface for pre‐heating by means of a 3D scanner optics. During pre‐heating, the laser power, the scanning speed and the number of cycles were varied. Welding with 4000 W and 2 m/min with a focused laser beam was executed. Thus the resulting temperature profile behind the ongoing laser beam and cooling time T 8|5 between 800 °C–500 °C was significantly extended. Two parameter combinations (15 cycles|600 W|50 mm/s( 2 ) and 10 cycles|800 W|50 mm/s 2 ) succeeded in a microstructure of bainite and martensite. By extending the cooling time T 8|5 to 3.11 s( 2 ) and 4.17 s 2 . Thus, average hardness for laser based pre‐tempering of 487 HV 0.5( 2 ) and 455 HV 0.5 2 was achieved. As a reference, global pre‐heating at 400 °C using a heating plate can reduce the average hardness of the weld zone from 729 HV 0.5 at room temperature to 304 HV 0.5 at a cooling time T 8|5 of 5.63 s. Abstract : Laser beam welding of heat‐treatable steel is challenging due to martensitic hardening. Before welding local laser pre‐tempering of the welding zone with an oscillating defocused laser beam is investigated. Therefore the beam was guided over the surface using a 3D scanner optics. Thus the cooling rates and the resulting martensitic structure within the melting and heat affected zone are reduced. Translation abstract: Es wird das laserbasierte Vorwärmen des Laserstrahlschweißens mit einer 3D‐Scan‐Optik, angewandt auf AISI 1045 Stahl, untersucht. Das Laserstrahlschweißen von Vergütungsstahl ist aufgrund der martensitischen Härtung in Kombination mit Defekten eine Herausforderung. Das Vorwärmen zielt auf die Reduzierung der Abkühlungsraten und des martensitischen Gefüges innerhalb der Schweißnaht. Zum Vorwärmen wurde ein oszillierender, defokussierter Laserstrahl mittels einer 3D‐Scanner‐Optik über die Oberfläche geführt. Während des Vorwärmens wurden die Laserleistung, die Scangeschwindigkeit und die Anzahl der Zyklen variiert. Es wurde mit 4000 W und 2 m/min bei fokussiertem Laserstrahl geschweißt. Dadurch wurde das resultierende Temperaturprofil hinter dem laufenden Laserstrahl und die Abkühlzeit T 8|5 zwischen 800 °C–500 °C deutlich verlängert. Zwei Parameterkombinationen (15 Zyklen|600 W|50 mm/s( 2 ) und 10 Zyklen|800 W|50 mm/s 2 ) führten zu einem Gefüge aus Bainit und Martensit. Durch die Verlängerung der Abkühlzeit T 8|5 auf 3, 11 s( 2 ) und 4, 17 s 2 wurde eine mittlere Härte für die laserbasierte Vorwärmung von 487 HV 0, 5( 2 ) und 455 HV 0, 5 2 erreicht. Als Referenz dient die globale Vorwärmung bei 400 °C mit einer Heizplatte. Die mittlere Härte der Schweißzone wird von 729 HV 0, 5 bei Raumtemperatur auf 304 HV 0, 5 bei einer Abkühlzeit T 8|5 von 5, 63 s reduziert.